Pengaruh Penerapan Strategi Keunggulan Bersaing, Total Quality Management, Cost of Quality, dan Sistem Akuntansi Manajemen Terhadap Kinerja Perusahaan (Studi Sensus Pada Perusahaan Manufaktur Bersertifikasi ISO 9000 di Jawa Timur) - Nasri, Mohammad (Jurnal Manajemen Akuntansi dan Bisnis, 2008)
This research aims to obtain empirical evidence and explanation about the influence of competitive advantage strategy application, Total Quality Management, Cost of Quality and Management Accounting System on manufacture performance getting the ISO 9000 certificate in East Java. The result of the hypothesis test show that the influence of competitive advantage strategy application to company performance is of 34%. Total quality management application influences company performance of 21%. The cost of quality application influences company performance of 45%. Management Accounting System Application influences company performance of 8%. Simultaneously, the influence of the competitive advantage strategy, Total Quality Management, Cost of Quality and Management Accounting System applications in company performance is 91%. The implication of this research is that the applications of competitive advantage Strategy, Total Quality Management, Cost of Quality and Management Accounting System are proven to give positive and significant contributions to company performance. Keywords: Â  competitive advantage strategy, total quality management, cost of quality, management accounting system, balance scorecard, ISO 9000, strategic business unit.